Russian Economic Report, No. 25, June 2011 : Securing Stability and Growth - World Bank (Washington, DC, 2017)
Russia has seen even higher oil windfall in the past few months, which translates into likely fiscal surpluses this year and next. The government should not miss the opportunity provided by a large oil windfall to substantially improve its long-term fiscal position, further reduce inflation, and, therefore, ensure a strong basis for durable stability and healthy growth in the future. Rising domestic demand and credit activity are increasingly supporting solid growth. Overall, labor market conditions improved recently while poverty was broadly flat during and after the crisis, but unemployment and poverty in many regions remain difficult. Further reductions in poverty will require greater policy focus and persistence in implementing more effective and targeted programs, especially in the poorest regions. Two new special-topic analyses focus on export diversification in Russia, and food and energy inflation in Europe and Central Asia region. In the first, results show that productivity is the key to exports and that lack of competition and entrepreneurial innovation are relevant obstacles to the emergence of new, potentially exportable products. In the second, it is shown that food and energy prices in Russia and other countries in Europe and Central Asia are contributing significantly to consumer price inflation, complicating anti-inflation policy and poverty reduction.